2012
DOI: 10.1074/jbc.m111.281303
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure and Molecular Interactions of Lamin B Receptor Tudor Domain

Abstract: Background: Lamin B receptor (LBR) is an integral nuclear envelope protein and contains a Tudor domain. Results:The NMR structure of LBR-Tudor was determined and its interactions with nuclear proteins, histones, and nucleosomes were explored. Conclusion: LBR-Tudor is not involved in recognition of methylated histones and binds free H3. Significance: Tudor domains may act as histone chaperone-like platforms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 60 publications
1
21
0
1
Order By: Relevance
“…In contrast, a tudor domain-deletion mutant, LBR ⌬1-53 , and the mutants in which aromatic residues were substituted with alanine, LBR W16A and LBR Y23A , moved ϳ7 times faster than the LBR WT (diffusion coefficients were 0.230 Ϯ 0.007, 0.253 Ϯ 0.007, and 0.267 Ϯ 0.006 m 2 /s, respectively). A similar result showing increased mobility of a tudor domain-deletion LBR mutant by FRAP analysis was also reported previously (15,33). Further experiments showed that alanine substitutions of tyrosine 41 and aspartic acid 43 in the histone code-reading pocket of the tudor domain (Fig.…”
Section: The Histone Modification-specific Binding Activity Of Lbr Issupporting
confidence: 72%
See 3 more Smart Citations
“…In contrast, a tudor domain-deletion mutant, LBR ⌬1-53 , and the mutants in which aromatic residues were substituted with alanine, LBR W16A and LBR Y23A , moved ϳ7 times faster than the LBR WT (diffusion coefficients were 0.230 Ϯ 0.007, 0.253 Ϯ 0.007, and 0.267 Ϯ 0.006 m 2 /s, respectively). A similar result showing increased mobility of a tudor domain-deletion LBR mutant by FRAP analysis was also reported previously (15,33). Further experiments showed that alanine substitutions of tyrosine 41 and aspartic acid 43 in the histone code-reading pocket of the tudor domain (Fig.…”
Section: The Histone Modification-specific Binding Activity Of Lbr Issupporting
confidence: 72%
“…A previous report showed that the LBR tudor domain binds to histone H3 but not to H4. However, the study also demonstrated that the RS domain of LBR can bind to histone H4 in vitro (15). We argue that the tudor domain is essential for recognition of the H4 modifications because NP W16A lacks histone modification binding specificity.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The N-terminal region of LBR comprises a Tudor domain (also called the globular I domain) and a globular II domain, which are linked by a hinge region (Liokatis et al, 2012; Ye et al, 1997). The hinge region contains a nuclear localization signal (NLS), which is required for the interaction with importin β (Ma et al, 2007), and an arginine-serine repeat (RS) domain, which consists of multiple repeats of arginine and serine residues (Sellis et al, 2012).…”
Section: Introductionmentioning
confidence: 99%